Five-week program to increase agility, speed and power in the preparation phase of a yearly training plan - Robinson, B. M.; Owens, B. (Strength and Conditioning Journal, 2004)
This feature presents a program that targets fundamental techniques and skills required for straight ahead speed, directional changes, and lower body power development to be used during a collegiate athlete's non-traditional season. The goal of the program is to teach generalized movement patterns and build a solid foundation that can be used by individual sport coaches during their traditional season